A cento anni dalla grande guerra. Effetti inattesi. Vol. 4 Le donne fra disciplina militare e nuove libertà - Pescarolo, Alessandra (Atti, 2017)
The volumes on World War I which are published here are the result of a series of seminars held at the Department of Political and Social Sciences of the University of Florence between 2014 and 2015. Starting from the occasion of the war's 100th anniversary, the authors wished to take stock of some specific aspects of the studies related to World War I. Historians, military analysts, political scientists and sociologists have also questioned the meaning of the fracture which inaugurated the 20th century and, consequently, the basic features of the new policy of the 'short century', in both an Italian and European perspective.